Suppression of uPA and uPAR Blocks Radiation-induced MCP-1 mediated Recruitment of Endothelial Cells and Monocytes in meningioma - Nalla, Arun Kumar (2011)
Chemokines play a vital role in recruiting various cell types in the process of tissue repair. Radiation, a major therapeutic modality in cancer treatment, has been described to induce inflammatory response that might lead to the expression of several chemokines. In the present study, we investigated the mechanism of monocyte chemoattractant protein-1 (MCP-1) induction by radiation in meningioma cell lines and the paracrine effect on human microvascular endothelial cells (HMEC). After radiation, meningioma cell lines (IOMM Lee and SF-3061) showed an increased expression of MCP-1. In addition, irradiated meningioma cancer cell conditioned medium (CM) showed increased ability to attract HMEC and stimulate MCP-1-induced protein (MCPIP), VEGF and angiogenin expression in HMEC. This chemotactic activity and angiogenic stimulator effect on HMEC was almost abrogated by depleting MCP-1 from the irradiated cancer cell CM. Further, inhibition of either ERK activation/expression or NF-κB nuclear translocation hindered radiation-induced MCP-1 expression in both meningioma cell lines. Further, supplementing cancer cells with exogenous ATF-uPA (with and without radiation) activated ERK phosphorylation, nuclear translocation of the NF-κB p65 sub-unit (Rel-A), and MCP-1 expression. Downregulation of uPA and uPAR, simultaneously by transfecting the cancer cells with bi-cistronic siRNA-expressing plasmid (pU) inhibited radiation-induced ERK activation, nuclear translocation of Rel-A, NF-κB DNA binding activity, and MCP-1 expression. In addition, pU- transfected cancer cells (with or without radiation) reduced radiation-induced MCP-1 and blocked the recruitment of other cell types during the inflammatory process induced by radiation both in in vitro and in vivo conditions.